Role of Combined Use of Adiponectin and hsCRP in Cardiovascular Risk in Pediatric Neurogenic Bladder - Joanna Bagińska-Chyży; Alicja Szymańska; Agata Korzeniecka-Kozerska (Children)
Background/Objectives: Myelomeningocele (MMC) is the most severe form of spina bifida, often accompanied by impaired motor function due to paralysis of the lower limbs, as well as neurogenic bladder (NB). These factors may contribute to nutritional disorders and cardiovascular diseases (CVDs) in the future. High-sensitivity CRP (hsCRP) is a positive marker of unstable atherosclerotic plaques and is commonly used in the diagnosis of CVDs. Adiponectin has an opposite, anti-inflammatory function. The aim of this study was to assess the risk of CVDs in a group of children with NB and a control group, based on serum levels of adiponectin, hsCRP, and lipid profiles. Methods: A prospective clinical estimation based on 87 children (67 NB, 20 control group) was conducted. Data collected from medical histories included the following: sex, age, anthropometric parameters (height, weight, BMI), level of spinal lesion, and activity according to Hoffer’s scale. Lipid profile values (cholesterol, HDL, LDL, triglycerides) were assessed using standard blood sample tests. hsCRP and adiponectin were measured using an ELISA kit. Results: A comparison of adiponectin and hsCRP levels revealed statistically significant differences between the NB group and the control. Additionally, significant correlations were identified between BMI and the biomarkers: hsCRP was positively associated with BMI, whereas adiponectin exhibited a negative association. The highest concentrations of hsCRP were detected in MMC patients with a Th lesion level and in non-walker patients. Conclusions: Elevated hsCRP may reflect increased cardiovascular risk in children with NB. While adiponectin levels were also altered, their association with cardiovascular risk appears more complex and may involve additional metabolic mechanisms.